Docetaxel plus gemcitabine versus gemcitabine in elderly patients with advanced non-small cell lung cancer and use of a geriatric assessment: Lessons from a prematurely closed Hellenic Oncology Research Group randomized phase III study. Issue 1 (January 2017) - Karampeazis, Athanasios; Vamvakas, Lambros; Kotsakis, Athanasios; Christophyllakis, Charalambos; Kentepozidis, Nikolaos; Chandrinos, Vassilios; Agelidou, Anna; Polyzos, Aris; Tsiafaki, Xanthi; Hatzidaki, Dora; Georgoulias, Vassilis
Abstract: Objectives: To compare first-line treatment with docetaxel plus gemcitabine (DG) versus gemcitabine (G) in elderly patients with advanced/metastatic non-small-cell lung cancer (NSCLC). Patients and Methods: Chemotherapy-naïve patients with inoperable stage IIIB/IV NSCLC, ≥ 70 years, with an ECOG performance status (PS) of 0–2 were enrolled. Patients were stratified by PS and disease stage and randomized to either DG (docetaxel 30 mg/m 2 plus gemcitabine 900 mg/m 2 i.v.) or G (gemcitabine 1200 mg/m 2 i.v.) on days 1 and 8, every 3 weeks. The study's primary end-point was overall survival (OS). Results: In this prematurely closed study, 106 patients with a median age of 75 years (range, 70–92) were enrolled (DG: n = 54; G: n = 52); 77 (73%) had stage IV disease and 18 (17%) a PS of 2. There was no difference in terms of median OS (14.6 vs 12.2 months; p = 0.121), progression-free survival (PFS) (3.4 vs 2.6 months; p = 0.757) and overall response rate (26.0% vs 15.4%; p = 0.233) between DG and G arm, respectively. Patients with an Instrumental Activities of Daily Living (IADL) score < 7 had significantly lower median OS (7.6 vs 15.4 months; p = 0.002) and median PFS (1.7 vs 4.4 months; p = 0.009) than patients with higher IADL score. The regimens were well tolerated with no significant difference in severe toxicity. Conclusion: DG and G demonstrated comparable efficacy in elderly patients with NSCLC and high IADL score was correlated with superior clinical outcome.